Degradation of lignin in cassava residue with Phanerochaete chrysosporium by solid state cultivation - Bin Xu; Huixing Li; Chaojun Du; Ying Wang; Bin Li (Functional Materials, 2016)
Cassava residue is a lignocellulosic waste byproduct in cassava-based ethanol production. Bioconversion of this waste to methane is one choice to solve its disposal problem. The bioconversion of lignocellulosic wastes could be enhanced through lignin degradation by solid state cultivation (SSC) with Phanerochaete chrysosporium. In this study, effects of moisture content, veratryl alcohol concentration and pH on lignin degradation of P. chrysosporium in solid cassava residue substrate cultivation were examined. Results showed that lignin degradation were significantly affected by moisture content and veratryl alcohol concentration. The optimal cultivation conditions for lignin degradation were pH 4.5, moisture content 66% and veratryl alcohol concentration 5.70 mM/kg. Within fourteen days of cultivation at these optimal conditions, lignin degradation mainly occurred in the first six days and lignin loss were 28.36±0.25%. Moreover, microscopic structure observation demonstrated that the structure of cassava residue was destroyed. The degradation of lignin and breakdown of the cassava residue structure by P. chrysosporium in SSC would provide a new approach to facilitate the bioconversion of cassava residue to methane in the future application.